Алани на правобережжі Середньої Волги у період раннього та розвинутого середньовічча (VI—XIII ст.) - Бубенок, О.Б. (Хазарский альманах, 2007)
According to the data of Archeology and written sources we can constant three migrations of the Nortern Caucasian origin Alans to the right bank of Middle Volga in the Medieval times: 1 ) in 5-6 centuries AD as a result of expansion of the Onogurs and Turkuts in the North Caucasus; 2) in the 8-th century AD as a result of policy of the Khazars. 3) in the second half of the 10-th century as a result of flight of the Alans from the Don region after the downfall of Khazar kaganate. The being of the Alans in the Volga region promoted to the spreading of Iranian origin ethnic name Mordva and Burtas there.